Health system strategies and responses to the effects of Climate Change in Sub-Saharan Africa: A scoping review - Chancy Skenard Chimatiro; Solange Mianda; Precious Hajison; Martina Lembani (PLoS ONE, 2026)
Background Climate change is now regarded as a global health challenge of the 21st century, posing a negative health risk to the population. Sub-Saharan Africa is disproportionately affected more than any other region worldwide. Mapping strategies and responses in Sub-Saharan Africa to address the impact of climate change on health systems is a starting point for understanding evidence-based decision-making and informing best practices. Methods We conducted a scoping review to identify health systems strategies and responses to the effects of climate change in Sub-Saharan Africa. Electronic database searches were conducted on African Index Medicus, PubMed, CINAHL, and Scopus. Covidence software was used to remove duplicates, blind study selection, and data extraction. We included peer-reviewed articles (original quantitative and qualitative studies, mixed methods studies, reviews, editorials, and commentaries) published between 2011 and 2025. All book chapters and grey literature publications (dissertations, conference proceedings, abstracts, and reports) that primarily focus on climate change strategies and responses without effects on health systems were excluded. The results were analysed using descriptive thematic analysis. Results Out of 11459 articles, 8 studies met our inclusion criteria. Most studies provided strategies and responses centered on service delivery, health workforce, health information, leadership and governance, with few on health financing and medicinal products. No study was identified that had outlined strategies and responses across all of the six World Health Organisation building blocks for the health systems. Implementation challenges identified include inadequate funding, lack of knowledge among health workers on climate change and health, inadequate surveillance and reporting structures, and low prioritization of climate change activities among health workers. Conclusions This scoping review has identified some health system strategies and responses to the effects of climate change within the Sub-Saharan African region. The review has revealed that existing strategies and responses are fragmented and hindered by some implementation challenges. As climate change continues to pose health threats to the global population, urgent and effective interventions are required to minimize its impacts. It is essential to understand the unique vulnerabilities of the health systems, particularly those in the Sub-Saharan African region. The time is now to develop strategies and responses that can improve and strengthen health systems as it protects health of the population from the effects of climate change.